Investigation of biomass depolymerization by surface techniques1. (21st January 2014) - Ruppert, A. M.; Grams, J.; Chełmicka, M.; Cacciaguerra, T.; Świerczyński, D.; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> The application of time‐of‐flight (ToF)‐SIMS to cellulose valorization is described. Cellulose samples subjected to ball milling or sulfuric acid impregnation, or combinations thereof, were subjected to hydrolysis. The material, which was impregnated in the last treatment step, no matter whether previously milled or not, exhibited the highest hydrolysis activity because of the highest accessibility of surface sulfonic groups. When milling followed impregnation, the activity was decreased because of possible encapsulation of sulfonic groups in the bulk. The ToF‐SIMS analysis revealed that both the ball mill and the stainless steel reactor may be a source of chromium and iron impurities, which can decrease the hydrolysis yield. Copyright © 2014 John Wiley & Sons, Ltd.